A new host [Centaurea stapfiana (Hand.-Mazz.) Wagenitz (Asteraceae)] record for the moth Metzneria subflavella Englert (Lepidoptera: Gelechiidae) from Turkey. (2nd January 2017) - Özaslan, Cumali; Bolu, Halil; Akın, Kesran
Abstract: The present study was carried out in vineyard fields of Diyarbakır province, Turkey, in 2014 on Centaurea stapfiana (Hand.-Mazz.) Wagenitz (Asteraceae) infested with the larvae of moth Metzneria subflavella Englert (Lepidoptera: Gelechiidae). Metzneria subflavella were obtained from C. stapfiana flower buds collected in vineyard fields. C. stapfiana is a new host record for M. subflavella . In addition, this is the first record of M. subflavella from insect fauna of Turkey.